2007
DOI: 10.1158/1055-9965.epi-07-0215
|View full text |Cite
|
Sign up to set email alerts
|

Serum Pepsinogen Levels,Helicobacter pyloriCagA Status, and Cytokine Gene Polymorphisms Associated with Gastric Premalignant Lesions in Costa Rica

Abstract: The detection of gastric premalignant lesions, atrophic gastritis, corpus atrophic gastritis, and intestinal metaplasia, using several potential markers was examined in Costa Rica. Depending on the lesion investigated, from a total of 223 dyspeptic patients, 58 (26.0%), 31 (13.9%), or 23 (10.3%) were histologically diagnosed with atrophic gastritis, corpus atrophic gastritis, or intestinal metaplasia, respectively. Sera were used for the measurement of pepsinogen (PG) and Helicobacter pylori CagA antibody (Cag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…In particular, IL-1β is important in initiating and amplifying the inflammatory response to H pylori infection, resulting in severe inflammation possibly leading to atrophic and metaplastic changes in the gastric mucosa. An association between cytokine polymorphisms in IL-1β and IL-1RN, and gastric premalignant lesions was previously reported in a Costa Rican population [33] , while carriers of IL-1β+3954_T/C and IL-1RN*2/L had an increased risk for developing gastric cancer in another Costa Rican study [34] . Likewise, our results showed that the prevalence of the proinflammatory genotypes IL-1β+3954_T/C and IL-1RN*2/L was significantly higher in gastric cancer cases than in non-cancer cases, supporting the association of polymorphisms within IL-1β and IL-1RN and gastric cancer in the Costa Rican population.…”
Section: Discussionmentioning
confidence: 55%
“…In particular, IL-1β is important in initiating and amplifying the inflammatory response to H pylori infection, resulting in severe inflammation possibly leading to atrophic and metaplastic changes in the gastric mucosa. An association between cytokine polymorphisms in IL-1β and IL-1RN, and gastric premalignant lesions was previously reported in a Costa Rican population [33] , while carriers of IL-1β+3954_T/C and IL-1RN*2/L had an increased risk for developing gastric cancer in another Costa Rican study [34] . Likewise, our results showed that the prevalence of the proinflammatory genotypes IL-1β+3954_T/C and IL-1RN*2/L was significantly higher in gastric cancer cases than in non-cancer cases, supporting the association of polymorphisms within IL-1β and IL-1RN and gastric cancer in the Costa Rican population.…”
Section: Discussionmentioning
confidence: 55%
“…After excluding 59 articles, we were left with a total of fifteen studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). From each study, we extracted information on publication year, country, race/ethnicity, description of sampling procedures including selection criteria, sample size, prevalence of H. pylori infection, outcome studied, reference group, criteria for histologic classification, polymorphisms studied, genotyping method, and respective quality control.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…Nonetheless, those patients who had undergone surgery for gastric malignancy would have exhibited precancerous lesions such as atrophic gastritis and IM, and the possibility of Elroy Patrick Weledji anastomotic recurrence is higher than for the patients who had undergone benign gastric surgery (38,49,52). At present, there are no other recognized good markers of gastric dysplasia or cancer and residual premalignant (type III) IM may be the only marker for anastomotic recurrence of gastric cancer (38,(53)(54)(55). Micro RNAs are currently being evaluated as a specific diagnostic and prognostic marker (55).…”
Section: Gastric Remnantmentioning
confidence: 99%
“…A 100% infection results in 6-fold increase in incidence of gastric cancer (14,37). The H. pylori that carry the Cag A gene product cytotoxin associated vacuolating antigen A (Vac A) also causes gastric B-cell mucosa-associated lymphoid tissue (MALT) lymphoma (38). Despite the fact that the stomach does not normally have any lymphoid tissue like the terminal ileal Peyer's patches from which lymphoid malignancy could arise, recent studies have demonstrated that up to 90% of the gastric MALT type lymphoma were associated with H. pylori infection.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
See 1 more Smart Citation